The health team’s performance in the context of violence under the perspective of community-based leaderships in Londrina (PR) - Amaro, Marcia Caroline Portela; Andrade, Selma Maffei de; Garanhani, Mara Lúcia (Saúde e Sociedade, 2008)
In the last few years Brazil has been experiencing an increase in urban violence. Particularly in the city of Londrina (state of Paraná), there has been a disturbing growth of violence rates which has caused the city leaderships to take action. The aim of this study is to investigate what community-based leaderships think about the health team's performance regarding the violence issue. The leaderships are from two regions on the periphery of Londrina which have different levels of community mobilization. This is a qualitative study that used the theoretical framework of the Social Representations and Bardin's content analysis technique. Semi-structured interviews were conducted with leaderships chosen through the "snowball" process or network sampling. Interviews were conducted until a saturation of social representations was reached, totaling 26 interviews, 13 in each researched area. Results showed that, in general, the health team's performance is considered poor by the community-based leaderships. In the region where the community is more proactive, this performance is more articulated, whereas in the less proactive one, the performance is more focused and violence against the health professional has been reported. This study shows that it is necessary for health teams to give more attention to the violence issue, forming partnerships with organized segments in the community.